Development of salutogenetic factors in mental health: Antonovsky’s sense of coherence and Bandura’s self-efficacy related to Derogatis’ symptom check list (SCL-90-R) - Jungaberle, Henrik; Grevenstein, Dennis (Health and quality of life outcomes, 2013)
The paper analyses how resilience factors and mental health problems interrelate in a 3-year-longitudinal study with 16-19 year olds.
Gesehen am 31.03.2021